2010
DOI: 10.1002/kpm.336
|View full text |Cite
|
Sign up to set email alerts
|

Studying the processes during implementation of enterprise systems

Abstract: This paper explores the processes that occur during the implementation of an enterprise system (ES). It seeks to identify the most prevalent and/or that which has the most impact on the implementation. Data was collected through a case study of a SAP implementation on the UK site of an international durables manufacturing company. The research questions focus on the method for capturing and analysing process related data, as well as on what the actual processes are. Communication was found to be the most preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…In this regard, it is worth considering that in all systems under study "there is an interaction of highly complex components (i.e., intelligent human beings)" (Newman et al, 2006), either as elements of the system under study, or as "enforcers" of the study itself. A recent study (Sedmak, 2010) found that communication is a key factor for successful implementation, which reinforces the notion that success of such initiatives depends on the integration of human resources. To achieve this, the implementation of an initiative presented in this work requires the involvement and full commitment of top management.…”
Section: Develop Specific Implementation Plan [Implementation Phase]supporting
confidence: 58%
See 1 more Smart Citation
“…In this regard, it is worth considering that in all systems under study "there is an interaction of highly complex components (i.e., intelligent human beings)" (Newman et al, 2006), either as elements of the system under study, or as "enforcers" of the study itself. A recent study (Sedmak, 2010) found that communication is a key factor for successful implementation, which reinforces the notion that success of such initiatives depends on the integration of human resources. To achieve this, the implementation of an initiative presented in this work requires the involvement and full commitment of top management.…”
Section: Develop Specific Implementation Plan [Implementation Phase]supporting
confidence: 58%
“…One of the main challenges for the integration of computer systems is that, usually, organizations integrate isolated information systems (Sharum & Sage, 2002), since "organizations often make these decisions without formal analysis of existing systems and processes or without the clear understanding of the new system's details" (Jukic, Jukic, & Velasco, 2009;OASIG, 1996). An approach which integrates organizational and technical change is perhaps missing in most organizations (Sedmak, 2010).…”
Section: Introductionmentioning
confidence: 99%